COMPARATIVE ANALYSIS OF THE DISPUTES ON THE QUESTION OF "FAITH" IN THE ORIGINAL WORKS OF ABU HANIFA (R.A.) IN THE EXAMPLE OF MULLA ALI AL-QARI (Academicia Globe: Inderscience Research, 2023)
In this work were reflected the views of Imam Abu Hanifa and Ali al-Qari on the issue of "faith" are reflected, and the opinions that excess or deficiency of faith are the foundations of faith and that action is not one of the foundations of faith, but one of its conditions. As an additional comment on the texts mentioned in the book "Fiqhul-Akbar", Ali al-Qari also mentioned the rulings of the Ahl al-Sunnah wal Jama'a creed regarding faith in the book "Sharhu Fiqhul" Akbar.